Transcription factor Sox10 orchestrates activity of a neural crest-specific enhancer in the vicinity of its gene. - Reiprich, Simone; Wegner, Michael; et al. (Nucleic Acids Research, 2012)
The Sox10 transcription factor is a central regulator of vertebrate neural crest and nervous system development. Its expression is likely controlled by multiple enhancer elements, among them U3 (alternatively known as MCS4). Here we analyze U3 activity to obtain deeper insights into Sox10 function and expression in the neural crest and its derivatives. U3 activity strongly depends on the presence of Sox10 that regulates its own expression as commonly observed for important developmental regulators. Sox10 bound directly as monomer to at least three sites in U3, whereas a fourth site preferred dimers. Deletion of these sites efficiently reduced U3 activity in transfected cells and transgenic mice. In stimulating the U3 enhancer, Sox10 synergized with many other transcription factors present in neural crest and developing peripheral nervous system including Pax3, FoxD3, AP2α, Krox20 and Sox2. In case of FoxD3, synergism involved Sox10-dependent recruitment to the U3 enhancer, while Sox10 and AP2α each had to bind to the regulatory region. Our study points to the importance of autoregulatory activity and synergistic interactions for maintenance of Sox10 expression and functional activity of Sox10 in the neural crest regulatory network. © 2011 The Author(s).
UnivIS-Import:2015-03-09:Pub.2012.med.IB.LPCIPDBI.transc